2005
DOI: 10.1002/jez.a.151
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytic amoebocyte sub populations in the perivisceral coelom of the sea urchinLytechinus variegatus (Lamarck, 1816)

Abstract: The echinoderms are deuterostomic animals with a nonspecific immune system similar to that of vertebrates. Among coelomocytes, phagocytic amoebocytes have a key role in the nonspecific immune response in sea urchin, being responsible for microorganisms elimination through phagocytosis and also for humoral secretions of a wide spectrum. Sub-populations of phagocytic amoebocytes (PA) have been previously described and two distinct sub populations in the oral (OR) and aboral (AB) regions of the perivisceral coelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 28 publications
0
8
1
6
Order By: Relevance
“…Foreign substances have been shown to induce phagocytosis in another sea cucumber species [46], as well as in the sea urchin [18, 47, 48] and the starfish larva [49] and adult [50]. Our results show that in H. glaberrima , other PAMPs (gram-positive bacteria and dsRNA) also activated the immune system.…”
Section: Discussionmentioning
confidence: 53%
“…Foreign substances have been shown to induce phagocytosis in another sea cucumber species [46], as well as in the sea urchin [18, 47, 48] and the starfish larva [49] and adult [50]. Our results show that in H. glaberrima , other PAMPs (gram-positive bacteria and dsRNA) also activated the immune system.…”
Section: Discussionmentioning
confidence: 53%
“…Our study identified granulocytes in peristomial membrane tissue in TEM after 2 weeks of time span. Thus, red spherule cells were involved with the inflammatory process in E. lucunter, different from other Brazilian sea urchin (L. variegatus) (Mangiaretta and Silva, 2001;Borges et al, 2005). These findings indicate potential differences in inflammatory response that require further investigation.…”
Section: Amoebocytes Ferritin Labelling Tissue Injury and Cell Migracontrasting
confidence: 48%
“…For these reasons, ferritin was chosen as an adequate marker for free amoebocytes in the perivisceral coelom of E. lucunter. Amoebocytes were later found (2 weeks) in the peristomial membrane of animals whose amoebocytes were marked by ferritin and the peristomial membrane was injected by India ink, thus showing the persistence of chronic inflammation in E. lucunter not established in L. variegatus (Mangiaretta and Silva, 2001;Borges et al, 2005).…”
Section: Amoebocytes Ferritin Labelling Tissue Injury and Cell Migramentioning
confidence: 98%
“…Other studies in different sea urchins also supported the existence of two distinct sub‐populations of amoebocytes. In Lytechinus Variegatus , Borges et al 22 found two distinct populations of amoebocytes in the aboral and oral region of the coelomic cavity. Density gradient centrifugation also separated two sub‐populations of amoebocytes in S. purpuratus and S. drobachiensis 21 , 23 .…”
Section: Discussionmentioning
confidence: 99%